Skin manifestations of pancreatic diseases - Kunovsky, Lumir; Dite, Petr; Brezinova, Eva; Sedlakova, Libuse; Trna, Jan; Jabandziev, Petr (Biomedical papers, 2022)
Although symptoms of pancreatic diseases such as pancreatitis, acute and chronic and, carcinoma of the pancreas are mainly gastrointestinal in nature, the extra-pancreatic symptoms are also important. These include skin symptoms, such as pancreatic panniculitis, acanthosis nigricans, livedo reticularis, necrolytic migratory erythema, cutaneous signs of hemorrhage, as in persons with severe acute pancreatitis, or the finding of cutaneous metastases of pancreatic carcinoma, which may be a sign of advanced disease. The pancreas is therefore one of those organs for which diagnosis and therapy are often multidisciplinary. In this review article, we summarize current knowledge of the possible skin manifestations of pancreatic disorders.
Keywords: acute pancreatitis; chronic pancreatitis; pancreatic cancer; skin lesions; pancreatic panniculitis; livedo reticularis; acanthosis nigricans; necrolytic migratory erythema